2021
DOI: 10.22373/share.v10i2.9098
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Financial Stability of Islamic Insurance Companies Listed on Indonesia Financial Services Authority

Abstract: Islamic insurance is an Islamic financial service that guarantees a participant's life, health, education, asset, and business. Some of them experienced a decline in their financial stability. This study aims to analyze the determinants of financial stability of Islamic insurance companies registered at the Indonesian Financial Services Authority (OJK) from 2014 to 2018. Thirty-eight data observations were acquired from eight full-fledged Islamic insurance businesses' financial reporting, analyzed using panel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The challenges require a regulatory framework established as a catalyst to drive supply and demand; low market penetration, insurance Islamization issues and inadequate product development of Islamic insurance, limited liability companies and issuance of qard hassan funds in Islamic reinsurance. Hendra (2021) analyzed the determinants of financial stability of Islamic insurance companies registered with the Indonesian Financial Services Authority (OJK) from 2014 to 2018. The results showed that financial stability was significantly influenced by investment, insurance premiums, independent boards, and institutional ownership.…”
Section: Hierarchy Chartmentioning
confidence: 99%
“…The challenges require a regulatory framework established as a catalyst to drive supply and demand; low market penetration, insurance Islamization issues and inadequate product development of Islamic insurance, limited liability companies and issuance of qard hassan funds in Islamic reinsurance. Hendra (2021) analyzed the determinants of financial stability of Islamic insurance companies registered with the Indonesian Financial Services Authority (OJK) from 2014 to 2018. The results showed that financial stability was significantly influenced by investment, insurance premiums, independent boards, and institutional ownership.…”
Section: Hierarchy Chartmentioning
confidence: 99%
“…Indian families, however, use responsibility agreements when making financial decisions, where the wife invests in the short-term money market. At the same time, the husband invests in riskier long-term investments like real estate (Sharma & Kota, 2019;Hendra, 2021).…”
Section: A Introductionmentioning
confidence: 99%
“…On the other hand, according to (Haqqi, 2014) However, according to (Hendra, 2021) there are also several insurance companies that are currently experiencing default problems such as Wanaartha, Bumiputera, Jiwasraya which should be used as lessons for the community, regulators, as well as the management and stakeholders of insurance companies.…”
Section: Introductionmentioning
confidence: 99%